A comprehensive review of malaysia airline system (MAS) - Abd Razak M.Z.; Ilias A. (2023)
Differentiation is defined as the process of adding a set of meaningful and valued differences to distinguish the company's offering from competitors' offerings (Kotler, 2003, p. 315). The created value as obtain from being difference is to enhance the standard, performance review and establishment of one's company. Therefore it's important to strategize company's differences in boosting up the profit, achievement and acknowledgement. The main purpose of the case study is to review and evaluate MAS's website by applying Seven Unique Differentiation Strategies to Online Businesses (site environment/ atmospherics, making the intangible tangible, building trust, efficiency and timely order processing, pricing, CRM and enhancing the experience). In this study, qualitative data from MAS's website was analyzed and discussed through proposed concise list of Seven Unique Differentiation Strategies to Online Businesses by Strauss and Frost, 2006. The study is expected to improve the differentiation of organization's image and service information availability and accessibility on the Web in future. Finally, Researches agree to look into further the changes that should be made to enhance the Air Asia website evaluations and that changes are pertaining to virtual tours, appealing the 3-D images, immediate customer response and better "On Time Acknowledgement" for MAS's CRM. Zulkeflee and Azleen, 2011.